2007
DOI: 10.1038/modpathol.3800966
|View full text |Cite
|
Sign up to set email alerts
|

Actinin-4 expression in ovarian cancer: a novel prognostic indicator independent of clinical stage and histological type

Abstract: Actinin-4 is an isoform of non-muscular a-actinin and actin-bundling protein. By enhancing cell motility, actinin-4 shows different biological properties from another isoform of non-muscular actinin 'actinin-1' and variable clinicopathological implications of actinin-4 have been demonstrated in some human malignancies such as breast cancers, lung cancers, and colorectal cancers. We herein described the clinicopathological and prognostic significance of actinin-4 expression in ovarian cancers. Actinin-4 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 33 publications
3
75
0
1
Order By: Relevance
“…Two core specimens, 2.0 mm in diameter, for each case were taken from these blocks and transferred to recipient blocks using a TMA Master tissue microarray (3DHistech, Budapest, Hungary). 8 …”
Section: Tissue Microarraymentioning
confidence: 99%
“…Two core specimens, 2.0 mm in diameter, for each case were taken from these blocks and transferred to recipient blocks using a TMA Master tissue microarray (3DHistech, Budapest, Hungary). 8 …”
Section: Tissue Microarraymentioning
confidence: 99%
“…5,11,12 Previously, using immunohistochemistry, we detected high actinin-4 protein expression in the cytoplasm in 52% (137 of 265 cases) of ovarian cancers, and this was significantly associated with a clinically advanced tumor stage, a serous adenocarcinoma histology, high-grade tumor histology, a high degree of residual tumor after initial surgery, and a poor patient outcome. 13 Multivariate analysis indicated that high actinin-4 expression can be a prognostic indicator that is independent of clinical stage and histologic subtype. 13 Therefore, as is the case in other solid cancers, the cytoplasmic accumulation of actinin-4 protein in ovarian cancer cells is suggested to be associated with tumor cell motility, invasiveness, and metastatic potential.…”
Section: 3mentioning
confidence: 99%
“…13 Multivariate analysis indicated that high actinin-4 expression can be a prognostic indicator that is independent of clinical stage and histologic subtype. 13 Therefore, as is the case in other solid cancers, the cytoplasmic accumulation of actinin-4 protein in ovarian cancer cells is suggested to be associated with tumor cell motility, invasiveness, and metastatic potential.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations